The impact of human capital on youth entrepreneurship success: a focus on business development support beneficiaries in Gauteng - Khoza, Ntuthuko (My University, 2020)
South Africa is ranked globally as a country with one of the highest number of unemployed youth, with 40.3 per cent currently not in employment, education, or training. Small, Medium, and Micro Enterprise (SMME) development, specifically youth owned business development is one of the priority areas of government as SMMEs are viewed as key drivers of economic growth, innovation, and job creation, as well as advancement of inclusive growth in the country. The purpose of this study was to ascertain the impact of human capital factors namely entrepreneurial education, business development support (BDS) training, and entrepreneurial experience on youth entrepreneurship success, with a focus on youth entrepreneurs who are BDS beneficiaries in Gauteng. The study measured entrepreneurship success as profitability, revenue generated, as well as the number of employees within the venture. The research adopted a positivist and a cross-sectional approach due to the limited period. A survey questionnaire was administered, utilising the Qualtrics software, to the youth entrepreneurs through the Catalyst for Growth platform. The responses received totalled 661, of which 515 responses qualified for further analysis; 90 per cent of respondents were black youth entrepreneurs. The three hypotheses tested the effect of human capital factors, namely entrepreneurial education, BDS training, and entrepreneurial experience, on entrepreneurial success. The effect of entrepreneurial education was inconclusive while BDS training had a significant, strong and positive effect, and entrepreneurial experience was strong, positive but insignificant.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management specialising in Entrepreneurship and New Venture Creation to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Wits business school, Johannesburg, 2020
Keywords: Human Capital; Business Development Support; SMMEs; Youth Entrepreneurship; Entrepreneurship; SDG-8: Decent work and economic growth